Sensemaking, institutions and crises of legitimacy: the case of Nike's sweatshop - Zheng, Xiaolan (2010)
The aim of this study is to explore the phenomenon of the legitimacy crisis. This is a variant of organizational crises which, although increasingly common and managerially relevant, is still under-explored. A legitimacy crisis signals a problematic relationship between the focal organization and its socio-institutional environment which calls for repairing of meaning. Having considered this, the study has developed a theoretical framework that integrates the sensemaking and institutional perspectives to investigate this phenomenon. To operationalize this theoretical framework, I have conducted a single longitudinal case study featuring Nike in the 1990s' sweatshop controversy, using a narrative approach and documenting the narrative unfolding of the crisis as the unit of analysis. An extensive collection of publicly accessible archival data constituted the bulk of the data base.